Endothelin-1 is increased in the plasma of patients hospitalised with Covid-19. (June 2022) - Abraham, George R.; Kuc, Rhoda E.; Althage, Magnus; Greasley, Peter J.; Ambery, Philip; Maguire, Janet J.; Wilkinson, Ian B.; Hoole, Stephen P.; Cheriyan, Joseph; Davenport, Anthony P.
Abstract: Virus induced endothelial dysregulation is a well-recognised feature of severe Covid-19 infection. Endothelin-1 (ET-1) is the most highly expressed peptide in endothelial cells and a potent vasoconstrictor, thus representing a potential therapeutic target. ET-1 plasma levels were measured in a cohort of 194 Covid-19 patients stratified according to the clinical severity of their illness. Hospitalised patients, including those who died and those developing acute myocardial or kidney injury, had significantly elevated ET-1 plasma levels during the acute phase of infection. The results support the hypothesis that endothelin receptor antagonists may provide clinical benefit for certain Covid-19 patients. Graphical abstract: Unlabelled Image Highlights: Dysregulation of endothelial function is a feature of severe Covid-19 infection. The endothelial peptide, ET-1 is a potential therapeutic target. Higher circulating ET-1 levels are associated with more severe infection. Endothelin receptor antagonists may be of clinical benefit in Covid-19.